1-(4-Methoxyphenyl)-4-(3-nitrophenyl)-3-phenoxyazetidin-2-one - Baktır, Zeliha (International Union of Crystallography, 2011)
In the title compound, C(22)H(18)N(2)O(5), the four-membered β-lactam ring is nearly planar, with a maximum deviation of 0.023 (2) Å for the N atom, and has long C—C distances of 1.525 (5) and 1.571 (5) Å. The mean plane of this group makes dihedral angles of 11.61 (19), 74.5 (2) and 72.3 (2)° with three aromatic rings. An intramolecular C—H⋯O hydrogen bond occurs. The packing of the molecules in the crystal structure is governed mainly by intermolecular C—H⋯O hydrogen-bonding and C—H⋯π stacking interactions. Furthermore, a π–π interaction [centroid–centroid distance = 3.6129 (19) Å] helps to stabilize the crystal structure.